Grandchildren and Their Grandparents' Labor Supply - Peter Rupert; Giulio Zanella (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2014)
We study how becoming a grandparent affects grandparents' labor supply. In a simple model of the allocation of time in which seniors care about their offspring's welfare and also value time spent with family children, the sign of the effect is ambiguous. Using data from the Panel Study of Income Dynamics we find evidence that becoming a grandparent causes a reduction of employed grandmother's hours of work. We identify a lower bound of about 190. This effect originates towards the bottom of the hours distribution (i.e., among women less attached to the labor market). For employed grandfathers, the effect is also negative, originates towards the top of the hours distribution (i.e., where overtime work is substantial), but is smaller and more imprecisely estimated than for women. We also find that for working grandmothers the effect is stronger the closer grandparents and grandchildren live and during the first years since becoming a grandparent (i.e., when the grandchildren are younger). The "extensive margin" of grandparenting (becoming a grandparent) turns out to be much more important in generating these effects than the corresponding "intensive" margin (having additional grandchildren).
Keywords: D19; J13; J14; J22; 330